Systemic Fear, Modern Finance and the Future of Capitalism - Shimshon Bichler; Jonathan Nitzan (The Bichler and Nitzan Archives, 2010)
Existing theories of political economy, liberal as well as Marxist, see capital as a dual entity. According to these theories, the "real" essence of capital consists of material/productive commodities, while the "financial" appearance of capital either accurately mirrors or fictitiously distorts this underlying reality. We reject this duality. Capital, we argue, is finance, and only finance. In its modern incarnation, capital exists as forward-looking capitalization, a universal financial ritual that discounts expected future earnings to a singular present value. The universality of this reduction makes capitalization the most supple power instrument ever known to humanity. Previously, distributive power was associated with clear socio-ecological distinctions – differences between king and subject, owner and slave, tiller and landlord, field and citadel, village and town. Capitalization flattens these qualitative features to the point of irrelevance. In principle, anyone can be a capitalist, and what distinguishes one capitalist from another is the quantity of their capitalization: the most powerful are those with the greatest capitalization (dominant capital), and those that hold that power achieve and augment it by increasing their capitalization faster than others (differential accumulation). In this way, capitalization crystallizes the power of capitalists to shape their world, as well as the resistance of those that oppose this power. It gauges the capitalists' success in directing production and consumption, in shaping ideology and culture, in affecting the law, public policy, conflict, war and even the environment. It is the all-encompassing algorithm that creorders – or creates the order – of the capitalist mode of power. The purpose of our paper is to examine the breakdown of this algorithm. To be sure, this type of inquiry is hardly novel. Marxists have long searched for objective signs of capitalist collapse, preliminary omens that would foretell the system's imminent disintegration. However, because of their dual conception of capital, they've tended to look for such signs in the so-called real sphere of production and consumption, while paying far less attention to finance, which, in their view, is merely a distorted mirror of that reality. But finance isn't a mirror of real capital; it is real capital – and indeed the only real capital. So if we want to look for signs of systemic crisis and possible disintegration, our search should begin here, in the very ritual of capitalization. The specific focus of the article is two historical ruptures of modern finance – the periods of 1929-1939 and 2000-2010. During both periods, capitalists abandoned the conventional forward-looking ritual of capitalization, resorting instead to the backward-looking posture of pre-modern finance. In our view, these rare episodes are of great importance for understanding the nature of capitalist confidence and the capitalists' ability to rule – as well as the possibility that this system of rule will collapse. Our inquiry seeks, first, to characterize key features of these episodes; second, to speculate on their causes; and third, to assess, however speculatively, what they might imply for the future of capitalism.
Keywords: 330; asset; pricing; capitalization; capitalism; collapse; complex systems; confidence in obedience; discounting; dominant ideology; fear of death; financial markets; forward-looking; modes of power; peak oil; systemic crisis